2020
DOI: 10.1002/smll.202000030
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin 2D Mesoporous TiO2/rGO Heterostructure for High‐Performance Lithium Storage

Abstract: Lithium‐ion batteries (LIBs) have been widely applied and studied as an effective energy supplement for a variety of electronic devices. Titanium dioxide (TiO2), with a high theoretical capacity (335 mAh g−1) and low volume expansion ratio upon lithiation, has been considered as one of the most promising anode materials for LIBs. However, the application of TiO2 is hindered by its low electrical conductivity and slow ionic diffusion rate. Herein, a 2D ultrathin mesoporous TiO2/reduced graphene (rGO) heterostru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 49 publications
2
29
0
Order By: Relevance
“…As shown in Figure 3a, the TiC@C‐TiO 2 composite exhibits a sharp Raman scattering peak at 154 cm −1 , corresponding to the E g 1 mode of anatase TiO 2 . [ 41,42 ] Other Raman scattering peaks are assigned to the E g 2 , B 1g 1 , B 1g 2 + A 1g , and E g 3 vibrational modes of anatase TiO 2 , [ 41,43 ] respectively. In addition, two characteristic D band (1343 cm −1 ) and G band (1602 cm −1 ) of carbon can be identified in the TiC@C‐TiO 2 sample (Figure 3b), [ 44 ] proving the existence of amorphous carbon within the C‐TiO 2 shell.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 3a, the TiC@C‐TiO 2 composite exhibits a sharp Raman scattering peak at 154 cm −1 , corresponding to the E g 1 mode of anatase TiO 2 . [ 41,42 ] Other Raman scattering peaks are assigned to the E g 2 , B 1g 1 , B 1g 2 + A 1g , and E g 3 vibrational modes of anatase TiO 2 , [ 41,43 ] respectively. In addition, two characteristic D band (1343 cm −1 ) and G band (1602 cm −1 ) of carbon can be identified in the TiC@C‐TiO 2 sample (Figure 3b), [ 44 ] proving the existence of amorphous carbon within the C‐TiO 2 shell.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S4 in the Supporting Information shows the Raman spectra of the TiC and p‐TiO 2 samples. The TiC sample shows three Raman scattering peaks at 257, 409, and 604 cm −1 , [ 45 ] respectively, while the p‐TiO 2 samples exhibit five Raman scattering peaks at 145, 199, 397, 517, and 638 cm −1 , corresponding to the E g 1 , E g 2 , B 1g 1 , B 1g 2 + A 1g , and E g 3 vibrational modes of anatase TiO 2 , [ 41–43 ] respectively. By comparison with the Raman spectrum of the TiC@C‐TiO 2 composite, it is found that both the TiC and p‐TiO 2 samples have no characteristic D band and G band of carbon, indicating the absence of amorphous carbon in these samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hierarchically porous TiO 2 /rGO hybrid anode material designed by Yu and coworkers [352] exhibited a reversible capacity of 250 mAh g −1 at 1C rate (1 C = 335 mA g −1 ) in the voltage range of 1.0-3.0 V. After 1000 cycles, stable capacities of 176 and 160 mAh g −1 were delivered at 5C and 500 cycles at 10C, respectively. An ultrathin mesoporous TiO 2 /rGO composite was obtained by Liang et al via a layer-by-layer process [353]. Several studies were attempted to enhance the performance of TiO 2 /rGO composites by doping with nitrogen.…”
Section: Molybdenum-based Oxide Compositesmentioning
confidence: 99%